The Degree of Employing Twenty-First Century Skills while Using Flipped Classroom Strategy in Teaching: A Content Analysis Study - Albediwi, Abdullah Abdulrahman (Dirasat: Educational Sciences, 2020)
This study aims to identify the degree of employing twenty-first century skills while using flipped classroom strategy in teaching. To achieve the objectives of the study, the researcher used a descriptive-analytical approach in its style of content analysis. The researcher adapted Al-Mansour study tool (2018) to build a content analysis questionnaire for the study. The paragraphs of the questionnaire consisted of (22) items distributed over three main skills, namely learning and innovation, digital culture, and profession and life. The study sample consisted of (27) studies out of (93) studies. The findings of this study showed that these skills helped in “providing learners with activities to support creative thinkning”, which was highly ranked by particpants of the study. It was also found that these skills help in “” creating positive attitudes in self learning”. However, the findings showed that these skills were not clearly found among learners. The study hence, recommends the necessity of helping teachers, faculty members, and those interested in the skills of the twenty-first century to acquire them, in addition to including these skills in the teaching process.